The Synthesis and Mutagenicity of 1-Nitrosopyrene and 1-Nitroso-8-Nitropyrene - Elkhouri, Charles (My University, 1985)
1-nitropyrene and 1,8-dinitropyrene are environmental pollutants and direct-acting mutagens in bacteria. Studies have shown that reduction of the nitro group is essential for the expression of the mutageneity of these compounds and the formation of covalent DNA adducts in Salmonella typhimurium. It has also been shown that the corresponding amino compounds are only slightly mutagenic. Since the reduction of nitro compounds to amino compounds must proceed via the nitroso and hydroxylamino intermediates, it has been proposed that the hydroxylamines derived from 1-nitropyrene and 1,8-dinitropyrene are the ultimate mutagens.
1-nitrosopyrene and 1-nitroso-8-nitropyrene were synthesized and reduced to their corresponding hydroxylamines with ascorbic acid. While 1-nitrosopyrene (50,226 rev/nmole) was 50X more potent than 1-nitropyrene (985 rev/nmole) in the Ames Test, 1-nitroso-8-nitropyrene (8,000 rev/nmole) was 10X less potent than 1,8-dinitropyrene (85,830 rev/nmole). The hydroxylamines derived from these compounds proved to be very labile species and could not be characterized.
Keywords: synthesis, mutagenicity, nitrosopyrene, nitroso, compounds